2015
DOI: 10.1017/s1092852915000310
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and impulsive aggression

Abstract: Aggression is a behavior with evolutionary origins, but is often both destructive and maladaptive in today's society. Research over the past several decades has confirmed the involvement of neurotransmitter function in aggressive behavior. This research has centered around the "serotonin hypothesis." As this literature continues to grow, guided by pre-clinical research and aided by the application of increasingly sophisticated neuroimaging methodology, a more complex picture has emerged. As current pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
98
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 67 publications
(95 reference statements)
7
98
0
8
Order By: Relevance
“…On the molecular level, serotonergic (Coccaro et al, 2015), neuropeptide (Coccaro et al, 1998), and inflammatory protein abnormalities have been linked to impulsive aggression. At the macro level, functional brain imaging studies have found evidence of exaggerated amygdala response to angry faces and diminished functional connectivity between the amygdala and orbitofrontal cortex (Coccaro et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…On the molecular level, serotonergic (Coccaro et al, 2015), neuropeptide (Coccaro et al, 1998), and inflammatory protein abnormalities have been linked to impulsive aggression. At the macro level, functional brain imaging studies have found evidence of exaggerated amygdala response to angry faces and diminished functional connectivity between the amygdala and orbitofrontal cortex (Coccaro et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Among the various neurochemical pathways putatively involved, the serotonin (5-hydoxytryptamine [5-HT]) system has been the focus of extensive investigations [13,14]. A parsimonious mechanistic neurobiological model linking the 5-HT system with aggression points to behavioral inhibition as a key mediator [14].…”
Section: Neurobiological Basis Of Aggressive/violent Behavior: Insighmentioning
confidence: 99%
“…Among the various neurochemical pathways putatively involved, the serotonin (5-hydoxytryptamine [5-HT]) system has been the focus of extensive investigations [13,14]. A parsimonious mechanistic neurobiological model linking the 5-HT system with aggression points to behavioral inhibition as a key mediator [14]. According to this model, a greater activity of the 5-HT system would correspond to a greater behavioral inhibition of the aggressive individual when confronted with threat or frustration [14].…”
Section: Neurobiological Basis Of Aggressive/violent Behavior: Insighmentioning
confidence: 99%
See 2 more Smart Citations